(untitled) (Conversatoria Linguistica, 2022)
The present paper analyses the fates of the Middle English synonyms of the adjective happy. The group of the examined words contains adjectives beneurous, benewred, felicious, gracious, seely and the key item happy. Focusing on their fates in the period under question, the study uses data from the Innsbruck Corpus of Middle English, a collection of 129 Middle English digitised texts, preserved in 159 files, to determine token frequency, text distribution and semantic changes of the examined adjectives. Other sources used in the study are Middle English Dictionary (MED), The Oxford English Dictionary (OED), Historical Thesaurus of English (HTE) and AntConc, a freeware corpus analysis program. The evidence from the Innsbruck Corpus of Middle English Prose shows considerable discrepancies in the token frequency of the analysed terms and the number of attestations employed in the sense ‘happy’. Although the position of the adjective gracious was extraordinarily strong (354 attestations), the termyielded only 13 attestations used in the sense under study. The marginal status of benewred (2 attestations)and lack of beneurous in the Middle English texts examined announce their loss at the end of the period.